Raíces y tubérculos en República Dominicana - Rodríguez de Paredes, M. (International Center for Tropical Agriculture, 1986)
The supply and demand of cassava, yam, sweet potato, cocoyam, and potato in the Dominican Republic are analyzed; cultivated land characteristics and availability, farmers' socioeconomic profile, cropping systems, yields, production costs and constraints, and required labor are indicated. Cassava is grown in association with beans, yams, sweet potato, and maize. Of the total cassava production 95 percent is consumed fresh; only 2-3 percent is processed into casabe. Rejects are given to animals. Government policies are also reviewed and research and training objectives are indicated. A national cassava course was held with CIAT's collaboration. (CIAT)